2004
DOI: 10.1002/anie.200460031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Manipulation of Orthogonally Protected Dendrimers: Building Blocks for Library Synthesis

Abstract: The synthesis of dendrimers containing up to six different functional groups by multistep one-pot reactions involving a selective manipulation and deprotection strategy is described by E. E. Simanek and M. B. Steffensen in their Communication on the following pages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 34 publications
0
64
1
Order By: Relevance
“…1,2 Our early targets commonly incorporated p-aminobenzylamine because of the significant differences in the reactivity of the amines of this group. That is, during a convergent synthesis, protecting group manipulations and functional group interconversions could be avoided because the benzylic amine would react preferentially (essentially exclusively) with the monochlorotriazine dendron being elaborated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Our early targets commonly incorporated p-aminobenzylamine because of the significant differences in the reactivity of the amines of this group. That is, during a convergent synthesis, protecting group manipulations and functional group interconversions could be avoided because the benzylic amine would react preferentially (essentially exclusively) with the monochlorotriazine dendron being elaborated.…”
mentioning
confidence: 99%
“…1 From these studies, aminomethylpiperidine emerged as a diamine linker of choice and was used extensively. 1,2,7,9,[15][16][17]19,20 Using competition experiments, the relative reactivity difference measured for the cyclic secondary amine and primary amine of aminomethylpiperidine is ~ 20 times. Theoretically, 5% of the product formed might derive from reaction of the monochlorotriazine dendron with the primary amine instead of the desired secondary amine.…”
mentioning
confidence: 99%
“…These disulfide groups readily underwent exchange with biotin, captopril, a small peptide sequence, or even a DNA oligonucleotide (67 and 68, Chart 16), although the characterization and purification of the latter were challenging, and no general protocols emerged. 37,84,85 Qualitative observations resulting from these experiments indicated that steric factors arising from the size of the substrate or the dendrimer influenced the degree of exchange that occurred. A related kinetic study of disulfide exchange on the periphery of other melaminederived dendrimers confirmed that the rate of exchange increases as the size of the dendrimer decreases (69-73, Chart 17).…”
Section: Biologically Relevant Moleculesmentioning
confidence: 97%
“…37 The inference to the potential utility of this dendrimer for drug delivery and related biological applications was based on the demonstration that the functional groups could be manipulated after the synthesis of the dendrimer with little formation of byproducts. The power of triazine chemistry is best exemplified in these targets.…”
Section: Nucleophilic Aromatic Substitutionmentioning
confidence: 99%
“…This limitation was offset by carrying latent functionality (in the form of orthogonal protecting groups) through the synthesis that could be manipulated. 10,11 Of greater issue, the repetitious coupling of smaller fragments into larger ones required that most of the mass be carried through the entire synthesis. Regardless, reasonable quantities of materials of high purity up to generation three could be obtained for evaluation.…”
Section: Introductionmentioning
confidence: 99%